Design of splints based on the NiTi alloy for the correction of joint deformities in the fingers - Puértolas, Sergio (BioMed Central, 2010)
BACKGROUND: The proximal interphalange joint (PIP) is fundamental for the functional nature of the hand. The contracture in flexion of the PIP, secondary to traumatisms or illnesses leads to an important functional loss. The use of correcting splints is the common procedure for treating this problem. Its functioning is based on the application of a small load and a prolonged stress which can be dynamic, static progressive or static serial. It is important that the therapist has a splint available which can release a constant and sufficient force to correct the contracture in flexion. Nowadays NiTi is commonly used in bio-engineering, due to its superelastical characteristics. The experience of the authors in the design of other devices based on the NiTi alloy, makes it possible to carry out a new design in this work - the production of a finger splint for the treatment of the contracture in flexion of the PIP joint. METHODS: Commercial orthosis have been characterized using a universal INSTRON 5565 machine. A computational simulation of the proposed design has been conducted, reproducing its performance and using a model "ad hoc" for the NiTi material. Once the parameters have been adjusted, the design is validated using the same type of test as those carried out on commercial orthosis. RESULTS AND DISCUSSION: For commercial splint the recovering force falls to excessively low values as the angle increases. Angle curves for different lengths and thicknesses of the proposed design have been obtained, with a practically constant recovering force value over a wide range of angles that vary between 30° and 150° in every case. Then the whole treatment is possible with only one splint, and without the need of progressive replacements as the joint recovers. CONCLUSIONS: A new model of splint based on NiTi alloy has been designed, simulated and tested comparing its behaviour with two of the most regularly used splints. Its uses is recommended instead of other dynamic orthosis used in orthopaedics for the PIP joint. Besides, its extremely simple design, makes its manufacture and use on the part of the specialist easier.